Analisa Potensi Gelombang Laut sebagai Sumber Energi Terbarukan Menggunakan Perangkat Oscillating Water Column (OWC) Di Wilayah Perairan Laut Timor - Jasron, Jahirwan Ut; Mangesa, Daud P.; Boimau, Kristomus; Tarigan, Ben V.; Maliwemu, Erich U.K.; Salombe, Mexin (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2022)
An in-depth study is needed on the use of alternative energy to overcome human energy needs. This study aims to analyze the potential of ocean wave energy that can be converted by the "Oscillating Water Column" device on the Kolbano coast as a renewable energy source. Kolbano Beach is located in Kolbano Village, Kolbano District, and TTS Regency (South Central Timor) East Nusa Tenggara Province with an area of​approximately 17 sq km stretch of Kolbano beach area facing the Indian Ocean so that the consistency of the wave height produced is quite large. The wave height is large enough to be used as an alternative power plant. This research was conducted in Kolbano coastal waters, data on wave height and wind speed from BMKG (Metrology, Climatology, and Geophysics Agency) Kupang City in 2019 – 2021m with wave heights ranging from 0.31 to 2.3 m and wind speeds ranging from 1 .05 to 8.48 Watts.